“Shortcoming” of the electron density in BCC binary and ternary alloys of FeCr (V, Mo, W) systems studied by positron annihilation method - Grafutin, Victor Ivanovich; Evstukhina, Irina Alexandrovna; Ermakov, Viktor Mikhailovich; Kolotushkin, Vladimir Pavlovich; Miloserdin, Viktor Yurievich; Mischenko, Andrey Yurievich; Samosadny, Viktor Timopheevich; Udovsky, Alexander Lvovich; Funtikov, Yuriy Viktorovich (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Alloys based on iron doped by different additions were investigated. Binary alloys containing chromium, molybdenum were investigated at the first stage. It was shown that results of doping by 0.8% molybdenum and tungsten are similar to those for the sample doped by 9%chromium. Ternary alloys containing chromium and less amounts of molybdenum, tungsten and vanadium were investigated as well. Similarity to properties of the alloy containing 0.8% molybdenum was observed for these alloys